PENTA cognitive-systemic model. From the strategic formulation to the implementation process (2019)
A complex socio-technical system is constituted by five interdependent elements: strategy, culture, resources, management and markets. The strategy should not be understood as independent in the formulation and implementation processes, given that the five pillars should be analyzed as a unit taking into account the strategy rising results that emerge from the pillars’ interdependence. This framework is known as PENTA and provides high conceptual potential to understand and transform the organization in a given moment.